Kvalita života seniorů v Pardubicích - Liedermanová, Ivana (Univerzita Pardubice, 2010)
My contribution deals with the contemporary demographic situation of the ageing process of people in Europe, as well as in the Czech Republic. It is necessary to investigate both economical and social impact in context of individual policies and to implement them into upcoming conceptions. Within the frame of the community plan of social and related services The City of Pardubice has a conception of work with seniors that will be changing with respect to the results of the upcoming research.
Keywords: seniors; process of ageing; social work; social care; community planning; life quality; demographic development